Redefining Spiritual Spaces in the Age of Technology Innovations and Pitfalls - Guenther, Stacey K.; Li, Xiaoan; Scheidt, Michelle A.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
Emerging technologies are entering every aspect of human life, including the spiritual realm. At the same time, spirituality has entered mainstream environments, including business, education, health and healing, and tech design. This provides an opportunity for technology and wisdom traditions to evolve together due to the widening audiences and worldviews. In this open access volume, an assembly of experts explores the intersection of spirituality and technology as they are emerging in a variety of contexts in our world. Through a mixture of philosophy, advocacy, presentation of research findings, and sharing of practices, this book illustrates technology$1 (Bs influence on spirituality and vice versa and its applications to management, strategy, and leadership. At the same time, contributing authors identify the surfacing pitfalls, shadow material, and areas that must be attended to during this time of evolving landscapes. Additionally, two of the chapters highlight virtual practices that focus on racial healing, which are of crucial import at this time in our collective history, and another two explore healing, justice, and liberation through the uses of technology. Written in a think-piece style, this book is accessible to those within and outside of academia. This is an open access book.s
Chapter1: Introduction The Evolution of Spirituality and Consciousness -- Part I owards Consciousness and Flourishing Well Being -- Chapter2: Digital Connection Human Connection and the Scaling of Well Being -- Chapter3: Global Consciousness and the Power of Virtual Spaces -- Chapter4: Embodying the Foundations for Tech that Support Healing Justice and Liberation -- Chapter5: Building Social and Spiritual Infrastructures for Collective Wisdom -- Part II The Changing Role of Technology in Spirituality and Spiritual Spaces -- Chapter6: Networking and Digital Religion as a New Approach to 21st Century Spirituality -- Chapter7: Digital Renewal -- Chapter8: Has the Future Already Been Colonized -- Chapter9: Reframing Groups -- Chapter10: Whole Self Development for Educators through the Forum Process -- Chapter11: The Conversation Circle -- Chapter12: Virtual Racial Healing in a Dual Pandemic -- Chapter13: Afterword The Spiritual Infrastructure of the Future.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Technological innovations; Business ethics; Psychology, Industrial; Innovation and Technology Management; Business Ethics; Work and Organizational Psychology